EFL LEARNERS’ DIGITAL STORYTELLING-BASED TASKS ON TIKTOK APPS: ENCOUNTERED PROBLEMS IN ELT LISTENING AND SPEAKING CLASSROOM - Lasi, Febronia; Din, Maaz Ud; Meomanu, Bernardino R.; Molo, Imanuel Aprian Antony (UICELL, 2023)
This study aims at finding out causes and problems solving encountered by the thirty EFL Learners of the third semester at the University of Timor (Unimor) Kefamenanu, NTT-Indonesia. To collect the data needed, the researcher applied descriptive qualitative study with questionnaire and interview based on the students’ story telling about their “Summer Vacation” on TikTok videos. A Semi-structured interview for data collection was applied to collect the data needed. The descriptive evidence indicated that mostly students encountered challenges on both linguistic and nonlinguistic issues when delivering their stories on TikTok apps. Typical languagerelated problems encompass inadequacies as such grammar used, words choices and or lack of vocabularies and still there few poor pronunciation. While the nonlinguistics problems encountered are anxiety & lack of confidence. The elements contributing to the issue of English speaking and listening in this investigation included diminished motivation, insufficient practice, and apprehension about committing errors. Addressing the challenges of English speaking and listening involves enhancing grammar improvement, pronunciation both British and American accents. Yet, the EFL learners believe that incorporating tasks based on digital storytelling enhances their motivation and facilitates the development of ideas and collaborate in pairs of self-evaluation on their TikTok videos as well as their chosen partners’ TikTok videos. This action done to see the students’ critical thinking in their interpretive and critical listening. Last but not least, the majority of students held a positive views regarding the use of TikTok apps in improving their listening and speaking skills. They expressed favorable sentiments, considering TikTok to be an engaging, fascinating, inspiring, and enjoyable tool for learning. Keywords: Digital Story-telling, EFL Learners, TikTok Apps